EFFECT OF THE ACCOUNTING INFORMATION SYSTEM'S EFFICACY IN THE FINANCIAL PERFORMANCE ASSESSMENT OF IRAQI INDUSTRIAL COMPANIES (World Economics and Finance Bulletin, 2024)
By identifying the effectiveness of accounting information systems in providing accounting information that leads to improved financial performance and the role of accounting information in improving the valuation of financial performance in industrial companies, the study aims to illustrate the impact of the system's effectiveness on the oversight and performance evaluation of Iraqi industrial companies. Iraqi industrial businesses were included in the study sample. The study group included all department heads, managers, administrative officials, and workers from Iraqi manufacturing enterprises. A thorough survey sample comprising all administrative executives, supervisors, accountants, accounting officers, and technicians was chosen from the study population. Four hundred and fifty questionnaires were sent out. A total of 439 surveys were returned. The research's hypothesis was that "there is a significant moral effect between the accounting information system and the monitoring and evaluation of performance in Iraqi industrial companies." The influence of accounting information systems and the improvement of financial performance in Iraqi industrial enterprises were discovered by the study. By increasing accounting information systems by one standard weight, financial performance is improved and corrected by 0.847, punching the calculated T value and lowering the error ratio to 0.041. (20.796 .)Because of their reliance on conventional methods and adoption of uniform accounting systems, which weaken preventive action in the performance and immunization of the company, the study recommends that companies improve the performance of the sample study by restructuring their financial system. This has a negative impact on the generation of profits and improved performance of companies .
Keywords: financial performance assessment; internal control; accounting information systems